2020
DOI: 10.1002/ecy.3181
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent effects of host patch traits on species composition in a stickleback parasite metacommunity

Abstract: A core goal of ecology is to understand the abiotic and biotic variables that regulate species distributions and community composition. A major obstacle is that the rules governing species distributions can change with spatial scale. Here, we illustrate this point using data from a spatially nested metacommunity of parasites infecting a metapopulation of threespine stickleback fish from 34 lakes on Vancouver Island, British Columbia. Like most parasite metacommunities, the composition of stickleback parasites … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 93 publications
(140 reference statements)
1
19
1
Order By: Relevance
“…Despite spatial heterogeneity in the distribution of parasite species (Bolnick et al, 2020b), we did not detect parasite-mediated spatially fluctuating selection. The Mantel test between the distance matrix of parasite community and the distance matrix of MHC variants across all populations suggested that the two matrices were not correlated (r = .089, p = .22, Figure 5).…”
Section: Fluctuating Selectioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Despite spatial heterogeneity in the distribution of parasite species (Bolnick et al, 2020b), we did not detect parasite-mediated spatially fluctuating selection. The Mantel test between the distance matrix of parasite community and the distance matrix of MHC variants across all populations suggested that the two matrices were not correlated (r = .089, p = .22, Figure 5).…”
Section: Fluctuating Selectioncontrasting
confidence: 74%
“…In total, 11.8% of the variation in parasite richness could be explained by habitat type, 4.9% could be explained by watershed (ANOVA, habitat term, p < 2e‐16), while 28.3% could be explained by sample site (ANOVA, watershed/site term, p < 2e‐16). Bolnick et al (2020) provide further analysis of ecological factors structuring the parasite metacommunity (diversity, composition, co‐occurrence) within and among lakes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations